2020
DOI: 10.3390/en13215806
|View full text |Cite
|
Sign up to set email alerts
|

Energy Sustainability of Rural Residential Buildings with Bio-Based Building Fabric in Northeast China

Abstract: Due to the cold winters in northeast China, the energy consumption of the rural residential buildings is much higher in this region than in other regions. In this study, the energy sustainability of bio-based wall construction is examined through applications in rural residential buildings. Comparisons of the energy sustainability of the bio-based wall constructions and the conventional wall constructions are evaluated using IESVE-2019 computational simulation. The results show notable reductions in heating en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Straw residues are potential sources of organic carbon and plant nutrients to improve soil organic matter dynamics, nutrient cycling, and the soil's physical environment. Compared with burning, cutting the straw and sending it back to the fields directly can avoid environmental pollution [37]. Meanwhile, all nutrients contained in the straw can be sent back to the soil in this way.…”
Section: Reducing Construction Waste and The Environmental Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Straw residues are potential sources of organic carbon and plant nutrients to improve soil organic matter dynamics, nutrient cycling, and the soil's physical environment. Compared with burning, cutting the straw and sending it back to the fields directly can avoid environmental pollution [37]. Meanwhile, all nutrients contained in the straw can be sent back to the soil in this way.…”
Section: Reducing Construction Waste and The Environmental Impactmentioning
confidence: 99%
“…This improvement is particularly advantageous given the average space heating demand of 140 kWh/m 2 /year for existing housing stocks in the UK [56]. Furthermore, Yin et al ( 2020) proposed an evaluation of energy sustainability of the buildings with straw-bale walls in China s rural areas, and the results showed that applying such structures can lower thermal consumption by 45.82-204.07 kWh/m 2 /year and reduce coal consumption by over 40% (Figure 4) [37].…”
Section: Reducing the Energy Requirementmentioning
confidence: 99%
“…Yin et al examined the energy sustainability of bio-based wall construction through applications in rural residential buildings in northeast China. They highlighted the effectiveness of bio-based wall construction in reducing heating energy requirements and can solve the problem caused by straw burning in northeast China [15]. These studies are typically based on a specific region to investigate the applicability of a particular technology, highlighting the significance of geographical factors in technology adaptation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(8) Type M utilizes the debris of dismantled old buildings or commonly used rural materials on the visible surface, adopting materials as carriers of memory and inheriting the collective consciousness that is contained within them (Appendix M). (15) Type N draws on abundant local natural resources in a perceptible way to construct buildings, showcasing the unique natural characteristics of the local area (Appendix N). ( 8)…”
Section: Types Of Locally Based Architectural Construction Strategies...mentioning
confidence: 99%
“…Relying on the research on the driving factors of urban construction land, scholars have divided the driving factors of rural residential land into socio-economic factors, transportation accessibility factors, and natural environmental factors [22,23]. In particular, the level of socio-economic development has affected the size of rural residential land, especially in the economically developed eastern coastal areas where the growth rate of rural residential land is much higher than that in the western regions [24]. The rapid expansion of rural residential land near the city is more prominent than that in remote mountainous areas.…”
Section: Introductionmentioning
confidence: 99%